Analysis of the Lecture Method in Junior High School Science Learning on Students’ Learning Motivation - Azka Safrida Khoirunnisa; Siti Fatima Azzahra; Nia Dwi Ramadani; Asna Rahma Auliya; Emeiliya Sufiani (PT. Komunitas Peneliti Alinea, 2026)
This study was conducted to analyze how the lecture method in science learning at the junior high school level can affect several important aspects of the student learning process such as students' interest and enthusiasm for the lecture method, as well as how this method has an impact on students' focus and concentration during learning. This study also evaluates the level of students understanding of material delivered trough the lecture method, so that it can measure its effectiveness and participation in learning as an important indicator of overall student engagement. This study uses a quantitative descriptive research method. Data collection was carried out by providing instruments in the form of response questionnaires to all students. The subjects in this study are grade VIII students of SMPN 1 Kamal, Bangkalan Regency with a total of 32 students. The results of the study showed that the lecture method received a positive response to the indicators of student motivation and enthusiasm for learning with a score percentage of 75%. The indicator of student interest in the material taught was categorized as less positive with a score percentage of 67%. Indicators of student focus and concentration during learning were categorized as less positive with a score percentage of 68%. The indicator of understanding of the material presented was categorized as less positive with a score percentage of 66%. The indicators of student activity and participation during learning were categorized as less positive with a score percentage of 68%.